Toner
By introducing wax and amorphous resin into the toner, adjusting the physical properties of the crystalline resin, the problem that it is difficult for toners to achieve low temperature fixability, heat resistance and wipe resistance in the prior art is solved, and the problem is realized. Efficient image fixing and durability.
Patent Information
- Application Number
- CN202011451516.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-12
- Filing Date
- 2020-12-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-12-10
AI Technical Summary
The prior art is difficult to achieve low temperature fixing, heat resistance and wipe resistance of toner simultaneously, especially when using crystalline resin as the binder resin, there is a shortage of heat resistance and wipe resistance of images.
By introducing wax and amorphous resin into the toner, the glass transition temperature and crystallization speed of the crystalline resin are adjusted, ensuring that the reelastic modulus ratio at 30°C and 50°C is between 0.30 and 1.00 and at the difference The temperature and heat absorption of exothermic and endothermic peaks are controlled in scanning calorimetry to improve the heat resistance and wipe resistance of the image.
The toner that is rapidly melted at low temperature has excellent low temperature fixing, heat resistance and wipe resistance, meeting the needs of printers and copiers for product quality improvement.
Smart Images

Figure BDA0002827145600000271 
Figure BDA0002827145600000281 
Figure BDA0002827145600000282
Abstract
Description
Technical Field
[0001] The present disclosure relates to a toner for developing an electrostatic latent image formed by a method such as an electrophotographic method, an electrostatic recording method, or a toner jet recording method to form a toner image. Background Art
[0002] In recent years, in order to support further power saving in printers and copiers, toners with excellent low-temperature fixability are required. In order to meet such needs, toners that melt quickly at a relatively low temperature, that is, toners with excellent rapid melting properties are preferred. In order to obtain toners with excellent rapid melting properties, toners using crystalline resins as binder resins have been studied.
[0003] Since the crystalline resin has the property of becoming solid due to the regular arrangement of molecules, when the crystalline resin is heated to a temperature at which the regular arrangement is loosened, the viscosity of the crystalline resin as a whole decreases sharply. As a result, a toner having excellent rapid melting property that melts quickly at low temperatures can be obtained while achieving excellent heat-resistant storage stability.
[0004] Against this background, Japanese Patent Application Laid-Open No. 2014-130243, Japanese Patent Application Laid-Open No. 2014-142632, WO 2018 / 110593, and Japanese Patent Application Laid-Open No. 2014-59359 each propose a toner using a binder resin including a crystalline resin. Summary of the invention
[0005] Meanwhile, printers and copiers have also attracted attention for uses other than office use, and there is a strong demand for improving the quality of the obtained products. In particular, the heat resistance and scratch resistance of the obtained products are required to exceed conventional performance. The scratch resistance in the present disclosure refers to the possibility that the image surface is scratched or less likely to peel off when rubbed.
[0006] Crystalline resins are excellent in rapid melting properties, but have low elasticity, and thus have the property of being easily broken as a resin. As a result, toners using crystalline resins as binder resins tend to have a potential for significant improvement in terms of scratch resistance of obtained images.
[0007] Japanese Patent Application Laid-Open No. 2014-130243 proposes a toner having a shell covering a core by using a crystalline resin as a binder resin. In addition, Japanese Patent Application Laid-Open No. 2014-142632 proposes a toner having a sea-island structure in which a sea portion including a crystalline resin as a main component and an island portion including a non-crystalline resin as a main component exist. Japanese Patent Application Laid-Open No. 2014-130243 and Japanese Patent Application Laid-Open No. 2014-142632 show that both low-temperature fixability and bending strength of an image are achieved with the above configuration.
[0008] However, in the toners described in Japanese Patent Application Laid-Open No. 2014-130243 and Japanese Patent Application Laid-Open No. 2014-142632, since the crystalline resin and the non-crystalline resin exist separately, the scratch resistance of the image has room for further improvement from the viewpoint of the susceptibility to breakage unique to the crystalline resin and the like.
[0009] Regarding this problem, the scratch resistance of the image can be improved by introducing a non-crystalline part into a crystalline resin and improving the elasticity of the resin. However, when the non-crystalline part is introduced into a crystalline resin, the crystallization of the crystalline part is hindered, so the crystallization speed is reduced. Therefore, the image after fixing cannot be fully cured, and the heat resistance of the image is reduced.
[0010] WO 2018 / 110593 describes that both low-temperature fixability and storage stability are achieved by using a polymer including a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms as an essential constituent monomer as a binder resin. However, no research has been conducted on the monomers used, particularly from the perspective of the crystallization rate of the crystalline resin, and there is room for further improvement in the heat resistance of the resulting image.
[0011] Japanese Patent Application Laid-Open No. 2014-59359 describes that both low-temperature fixability and heat resistance of images are achieved by using a binder resin containing a crystalline resin and also using a nucleating agent. However, the crystallization speed is insufficient, and as a result, from the perspective of toner performance currently required, both low-temperature fixability and heat resistance of images need to be further improved.
[0012] For these reasons, in a toner using a crystalline resin as a binder resin, it is difficult to simultaneously achieve scratch resistance of an image, heat resistance of an image, and low-temperature fixing property.
[0013] The present disclosure provides a toner that solves such problems.
[0014] That is, the present disclosure provides a toner having low-temperature fixability, heat resistance of an image, and scratch resistance of an image.
[0015] The present disclosure is a toner including toner particles containing a crystalline resin, wherein
[0016] When, in the dynamic viscoelasticity measurement of the toner, the complex modulus of elasticity at 30° C. is represented by G*(30) and the complex modulus of elasticity at 50° C. is represented by G*(50), the following is satisfied:
[0017] 1.00≥G*(50) / G*(30)≥0.30,
[0018] And when
[0019] In differential scanning calorimetry of toner,
[0020] The peak temperature of the exothermic peak derived from the crystalline resin in the process of cooling after the temperature is raised to 150°C is represented by Tc (°C).
[0021] In the temperature increase process after the temperature decrease process, the peak temperature of the endothermic peak derived from the crystalline resin is represented by Tm (° C.), and
[0022] When the heat absorption is expressed by ΔH (J / g),
[0023] Tm is 50.0 to 80.0°C,
[0024] ΔH is 35 to 60 J / g, and
[0025] Tm-Tc is 0.0 to 7.0°C.
[0026] The present disclosure is a toner including toner particles containing a crystalline resin and a wax, wherein
[0027] When, in the dynamic viscoelasticity measurement of the toner, the complex elastic modulus at 30° C. is represented by G*(30) and the complex elastic modulus at 50° C. is represented by G*(50), the following is satisfied:
[0028] 1.00≥G*(50) / G*(30)≥0.30,
[0029] The amount of the wax in the toner particles is 1 to 20 parts by mass relative to 100 parts by mass of the crystalline resin; and
[0030] And when
[0031] In differential scanning calorimetry of toner,
[0032] During the cooling process after heating to 150°C, the peak temperature of the maximum exothermic peak is represented by Tc' (°C).
[0033] In the heating process after the cooling process, the peak temperature of the maximum endothermic peak is represented by Tm' (℃),
[0034] When the heat absorption is expressed by ΔH'(J / g),
[0035] Tm' is 50.0 to 80.0°C,
[0036] ΔH' is 35 to 60 J / g, and
[0037] Tm'-Tc' is 0.0 to 7.0°C.
[0038] According to the present disclosure, a toner having low-temperature fixing property, heat resistance of an image, and scratch resistance of an image can be provided.
[0039] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0040] In the present disclosure, unless otherwise specified, the description "XX or more and YY or less" or "XX to YY" indicating a numerical range refers to a numerical range including the lower limit and the upper limit as endpoints. In addition, the measurement method of each physical property will be described below.
[0041] When describing a numerical range step by step, the upper limit and the lower limit of each numerical range can be arbitrarily combined.
[0042] "Monomer unit" refers to the reaction form of a monomer substance in a polymer. For example, a carbon-carbon bond portion in the main chain in which a vinyl monomer in a polymer is polymerized is defined as one unit.
[0043] The crystalline resin refers to a resin showing a clear endothermic peak in differential scanning calorimetry.
[0044] A first toner of the present disclosure is a toner including toner particles containing a crystalline resin, wherein
[0045] When, in the dynamic viscoelasticity measurement of the toner, the complex elastic modulus at 30° C. is represented by G*(30) and the complex elastic modulus at 50° C. is represented by G*(50), the following is satisfied:
[0046] 1.00≥G*(50) / G*(30)≥0.30,
[0047] And when
[0048] In differential scanning calorimetry of toner,
[0049] The peak temperature of the exothermic peak derived from the crystalline resin in the process of cooling after the temperature is raised to 150°C is represented by Tc (°C).
[0050] In the temperature increase process after the temperature decrease process, the peak temperature of the endothermic peak derived from the crystalline resin is represented by Tm (° C.), and
[0051] When the heat absorption is expressed by ΔH (J / g),
[0052] Tm is 50.0 to 80.0°C,
[0053] ΔH is 35 to 60 J / g, and
[0054] Tm-Tc is 0.0 to 7.0°C.
[0055] A second toner of the present disclosure is a toner including toner particles containing a crystalline resin and a wax, wherein
[0056] When, in the dynamic viscoelasticity measurement of the toner, the complex elastic modulus at 30° C. is represented by G*(30) and the complex elastic modulus at 50° C. is represented by G*(50), the following is satisfied:
[0057] 1.00≥G*(50) / G*(30)≥0.30,
[0058] The amount of the wax in the toner particles is 1 to 20 parts by mass relative to 100 parts by mass of the crystalline resin; and
[0059] And when
[0060] In differential scanning calorimetry of toner,
[0061] During the cooling process after heating to 150°C, the peak temperature of the maximum exothermic peak is represented by Tc' (°C).
[0062] In the temperature-raising process after the temperature-lowering process, the peak temperature of the maximum endothermic peak is represented by Tm' (°C), and
[0063] When the heat absorption is expressed by ΔH'(J / g),
[0064] Tm' is 50.0 to 80.0°C,
[0065] ΔH' is 35 to 60 J / g, and
[0066] Tm'-Tc' is 0.0 to 7.0°C.
[0067] Here, since the amount of wax in the toner particles in the second toner is smaller than that of the crystalline resin, the peak temperature Tc' of the maximum exothermic peak, the peak temperature Tm' of the maximum endothermic peak, and the endothermic amount ΔH' are treated as being derived from the crystalline resin.
[0068] In differential scanning calorimetry (hereinafter, also referred to as DSC measurement) of the toner, when the peak temperature of the exothermic peak derived from the crystalline resin in the temperature drop process after the temperature rise to 150° C. is represented by Tc, and the peak temperature of the endothermic peak derived from the crystalline resin in the temperature rise process after the temperature drop process is represented by Tm, the difference Tm-Tc between Tm and Tc is used as an index of the crystallization rate. In addition, the amount of endothermic heat derived from the crystalline resin in the temperature rise process after the temperature drop process is defined as ΔH.
[0069] Here, Tm represents the melting point of the crystalline resin, and Tc represents the crystallization temperature of the crystalline resin.
[0070] When the toner particles do not contain wax, or when the peak temperature of the exothermic peak derived from the crystalline resin, the peak temperature of the endothermic peak derived from the crystalline resin, and the amount of endothermic heat derived from the crystalline resin are significantly different from the peak temperature of the exothermic peak derived from the wax, the peak temperature of the endothermic peak derived from the wax, and the amount of endothermic heat derived from the wax, respectively, Tc, Tm, and ΔH derived from the crystalline resin can be specified.
[0071] However, when the peak temperature of the exothermic peak derived from the crystalline resin, the peak temperature of the endothermic peak derived from the crystalline resin, and the amount of endothermic heat derived from the crystalline resin are close to the peak temperature of the exothermic peak derived from the wax, the peak temperature of the endothermic peak derived from the wax, and the amount of endothermic heat derived from the wax, respectively, and it is difficult to distinguish therefrom, Tc', Tm', and ΔH' are obtained in the following manner.
[0072] When the amount of the wax in the toner particles is 1 part by mass to 20 parts by mass relative to 100 parts by mass of the crystalline resin, in DSC measurement of the toner, in the temperature drop process after the temperature is raised to 150° C., the peak temperature of the maximum exothermic peak is represented by Tc′, in the temperature increase process after the temperature drop process, the peak temperature of the maximum endothermic peak is represented by Tm′, and the amount of endothermic heat is represented by ΔH′.
[0073] The slower the crystallization speed of a crystalline resin, the lower the crystallization temperature, because crystal nuclei are not generated unless the resin is cooled to a lower temperature. As a result, the value of Tm-Tc or Tm'-Tc' tends to increase.
[0074] For example, when the crystalline resin in the binder resin has a crystalline part and a non-crystalline part, as the amount of the non-crystalline part in the crystalline resin increases, the crystallization rate decreases so that the value of Tm-Tc or Tm'-Tc' tends to increase.
[0075] At the same time, the more the amount of crystalline sites in the crystalline resin, the faster the crystallization speed, so that the value of Tm-Tc or Tm'-Tc' tends to decrease. The smaller the value of Tm-Tc or Tm'-Tc', the faster the curing of the image after fixing, so that excellent heat resistance of the image tends to be obtained.
[0076] There are many ways to achieve the above physical properties. For example, in the case of a toner containing a crystalline resin having a crystalline portion and a non-crystalline portion in the binder resin, the heat resistance of the image is improved by lowering the glass transition temperature (hereinafter, referred to as Tg) of the crystalline resin. This property is improved, and compatibility with other properties is better achieved.
[0077] Generally, the lower the Tg of the binder resin, the softer the toner is at a lower temperature, and thus the heat resistance of the toner and the image is reduced. However, it is found that in a toner containing a crystalline resin having a crystalline part and a non-crystalline part in the binder resin, the lower the Tg of the crystalline resin, the higher the crystallization speed of the crystalline resin (the value of Tm-Tc or Tm'-Tc' tends to be smaller). This is apparently because when the Tg of the crystalline resin is higher than the temperature at which the crystalline resin crystallizes, the molecular motion of the crystalline resin is constrained by the non-crystalline part, and the crystallization speed is reduced.
[0078] As a result, it can be seen that, in the toner using a crystalline resin as the binder resin, the lower the Tg of the crystalline resin is, the higher the heat resistance of the image tends to be.
[0079] Meanwhile, when G*(50) / G*(30) is 0.30 to 1.00, this means that the change in elastic modulus at the storage temperature of the image is small. To achieve this, for example, Tm or Tm' is set to 50.0°C to 80.0°C, and at the same time, the Tg of the crystalline resin is increased to a certain extent.
[0080] When the complex elastic modulus at 30° C. is G*(30) and the complex elastic modulus at 50° C. is G*(50) in dynamic viscoelasticity measurement of the toner, the toner of the present disclosure satisfies the following formula.
[0081] 1.00≥G*(50) / G*(30)≥0.30
[0082] Here, G*(50) / G*(30) is used as an index of heat resistance of an image. A large value of G*(50) / G*(30) means that the change in complex elastic modulus from 30° C. to 50° C. is small and the hardness of the toner can be maintained.
[0083] When G*(50) / G*(30) is 0.30 or more, excellent heat resistance of an image can be obtained. G*(50) / G*(30) is preferably 0.40 to 1.00, and more preferably 0.50 to 1.00.
[0084] G*(50) / G*(30) can be controlled by changing Tm or Tm', or Tg of the crystalline resin, or by using a monomer capable of forming a non-crystalline site for the crystalline resin.
[0085] In the toner of the present disclosure, Tm or Tm' is 50.0°C to 80.0°C.
[0086] When Tm or Tm' is 50°C or more, excellent heat resistance of the image can be obtained. In addition, when Tm or Tm' is 80.0°C or less, excellent low-temperature fixability can be obtained. Tm or Tm' is preferably 50.0°C to 75.0°C, and more preferably 50.0°C to 70.0°C. Tm or Tm' can be controlled by the kind and content ratio of the monomer used in the crystalline resin.
[0087] The ΔH or ΔH' of the toner of the present disclosure is 35 J / g to 60 J / g. When ΔH or ΔH' is 35 J / g or more, excellent low temperature fixability can be obtained. When ΔH or ΔH' is 60 J / g or less, excellent scratch resistance of the image can be obtained. ΔH or ΔH' is preferably 35 J / g to 55 J / g, and more preferably 35 J / g to 50 J / g.
[0088] ΔH or ΔH′ can be controlled by the amount of the crystalline resin in the toner particles, the kind and content ratio of the monomer used in the crystalline resin, and the like.
[0089] The toner of the present disclosure has Tm-Tc or Tm'-Tc' of 0.0°C to 7.0°C. When Tm-Tc or Tm'-Tc' is within this range, excellent heat resistance of an image may be obtained. Tm-Tc or Tm'-Tc' is preferably 0.0°C to 6.5°C, and more preferably 0.0°C to 6.0°C.
[0090] Tm-Tc or Tm'-Tc' can be controlled by the amount of the crystalline resin in the toner particles, the composition and physical properties of components other than the crystalline resin, Tg of the crystalline resin, and the like.
[0091] Furthermore, as described later, the kind of monomer used for the crystalline resin is selected from the viewpoint of the SP value and Q value of each monomer, and design can be performed so that Tm-Tc or Tm'-Tc' of the crystalline resin has a desired value.
[0092] In addition, the Tc or Tc' of the toner of the present disclosure is preferably 40.0°C to 80.0°C, and more preferably 48.0°C to 75.0°C. When Tc or Tc' is within the above range, the crystallinity of the obtained image can be sufficiently improved, so that excellent heat resistance of the image can be obtained. Tc or Tc' can be controlled by the amount of crystalline resin in the toner particles, the composition and physical properties of components other than the crystalline resin, and the Tg of the crystalline resin, etc.
[0093] A toner that simultaneously achieves all of these physical properties is unknown in the art, and more favorable physical properties can be achieved by introducing an idea opposite to the conventional method of lowering the Tg of a crystalline resin.
[0094] The following embodiments of the toner of the present disclosure are preferred.
[0095] The crystalline resin comprises a monomer unit derived from the monomer (a),
[0096] Monomer (a) is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, and
[0097] The content ratio N(a) of the monomer unit derived from the monomer (a) in the crystalline resin is 30% by mass to 60% by mass.
[0098] The crystalline resin having a monomer unit derived from a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms is a side chain crystalline resin in which the chain hydrocarbon group as a side chain is partially crystallized. Therefore, the crystallization speed is faster than that of a foldable-crystal-type crystalline resin such as a crystalline polyester. As a result, better heat resistance of an image can be obtained.
[0099] When the content ratio N(a) of the monomer unit derived from the monomer (a) in the crystalline resin is 30% by mass or more, the rapid melting property is excellent and good low-temperature fixability can be obtained. In addition, when the content ratio is 60% by mass or less, a toner having excellent scratch resistance of the image can be obtained. The content ratio N(a) of the monomer unit derived from the monomer (a) is more preferably 30% by mass to 50% by mass.
[0100] Examples of the (meth)acrylate having an alkyl group having 18 to 36 carbon atoms include (meth)acrylate having a straight-chain alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, lauryl (meth)acrylate, hexacosyl (meth)acrylate, octadecyl (meth)acrylate, triacontyl (meth)acrylate, and tridodecyl (meth)acrylate, etc.], and (meth)acrylate having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].
[0101] Among them, from the viewpoint of heat storage resistance and low temperature fixing property of an image, at least one selected from the group consisting of (meth)acrylates having a linear alkyl group having 18 to 36 carbon atoms is preferred, at least one selected from the group consisting of (meth)acrylates having a linear alkyl group having 18 to 30 carbon atoms is more preferred, and at least one selected from the group consisting of stearyl (meth)acrylate and behenyl (meth)acrylate is even more preferred.
[0102] The toner particles may include a known resin other than the crystalline resin as a binder resin, but the amount of the crystalline resin in the toner particles is preferably 60% by mass to 100% by mass. When the amount is 60% by mass or more, the characteristics of the toner using the crystalline resin as the binder resin can be obtained, so that even better low-temperature fixability and heat resistance of the image can be obtained. The amount of the crystalline resin in the toner particles is more preferably 65% by mass to 90% by mass.
[0103] As the resin other than the crystalline resin, a resin generally used for toner can be used as a binder resin, and examples thereof include polyester resins, styrene acrylic resins, polyamide resins, furan resins, epoxy resins, xylene resins, silicone resins, and the like.
[0104] The glass transition temperature of the crystalline resin is preferably 50° C. to 90° C. When the glass transition temperature of the crystalline resin is 50° C. or higher, the resin is less likely to soften even at storage temperature, so that even better heat resistance of the image can be obtained. In addition, when the glass transition temperature of the crystalline resin is 90° C. or lower, the crystallization speed of the crystalline resin increases, so that the value of Tm-Tc or Tm'-Tc' can be reduced. As a result, better heat resistance of the image can be obtained.
[0105] The glass transition temperature is preferably 60° C. to 85° C., and more preferably 65° C. to 80° C. The glass transition temperature can be controlled by the kind and content ratio of the monomers used in the crystalline resin.
[0106] The following embodiments of the toner of the present disclosure are also preferred.
[0107] The crystalline resin further comprises a monomer unit derived from the monomer (b),
[0108] When the SP value of the monomer unit derived from monomer (a) is changed from SP(a) (J / cm 3 ) 0.5 The SP value of the monomer unit derived from monomer (b) is represented by SP(b) (J / cm 3 ) 0.5 When expressed, the following is satisfied:
[0109] SP(b)-SP(a)≥4.0,
[0110] Furthermore, in the crystalline resin, the content ratio N(b) of the monomer units derived from the monomer (b) in all the monomer units other than the monomer units derived from the monomer (a) is 50% by mass to 100% by mass.
[0111] Satisfying SP(b)-SP(a)≥4.0 means polarity separation of the monomer units derived from monomer (a) and the monomer units derived from monomer (b). Due to the polarity separation of the monomer units derived from monomer (a) and the monomer units derived from monomer (b), it is unlikely that the monomer units derived from monomer (a) and the monomer units derived from monomer (b) are mixed, and these monomer units exist in the crystalline resin in a microscopic phase-separated state.
[0112] As a result, the concentration of the monomer unit derived from the monomer (a) is locally increased, and the crystallization speed of the crystalline resin is improved, so that better heat resistance of the image can be obtained. SP(b)-SP(a) is preferably 5.0 or more, and more preferably 6.0 or more.
[0113] Furthermore, when N(b) is 50% by mass or more, the above-mentioned effect is further enhanced, and more excellent heat resistance of the image can be obtained. N(b) is more preferably 50.0% by mass or more and 85.0% by mass or less.
[0114] SP(a) and SP(b) are determined by the molecular structures of monomer (a) and monomer (b).
[0115] SP(a) is preferably 17.5 (J / cm 3 ) 0.5 to 19.0(J / cm 3 ) 0.5 , and more preferably 18.0 (J / cm 3 ) 0.5 to 18.5(J / cm 3 ) 0.5 .
[0116] SP(b) is preferably 22.0 (J / cm 3 ) 0.5 to 29.5(J / cm 3 ) 0.5 , and more preferably 24.0 (J / cm 3 ) 0.5 to 26.5(J / cm 3 ) 0.5 .
[0117] When a plurality of monomers satisfying the requirements of the monomer (a) are present in the crystalline resin, the value of SP(a) is a weighted average value of the SP values of the monomer units.
[0118] For example, when a monomer unit derived from monomer (a) having an SP value of SP1(a) is included at A mol% based on the number of moles of all monomer units satisfying the requirement of the monomer unit derived from monomer (a), and a monomer unit derived from monomer (a) having an SP value of SP2(a) is included at (100-A) mol% based on the number of moles of all monomer units satisfying the requirement of the monomer unit derived from monomer (a), SP(a) is
[0119] SP(a)=(SP1(a)×A+SP2(a)×(100-A)) / 100.
[0120] When three or more monomer units satisfying the requirements for the monomer unit derived from monomer (a) are contained, similar calculation is performed.
[0121] Meanwhile, monomer (b) corresponds to all monomer units satisfying the following formula with respect to SP(a) calculated by the above method.
[0122] SP(b)-SP(a)≥4.0
[0123] That is, when a plurality of monomers (b) are present, SP(b) represents the SP value of a monomer unit derived from each monomer, and SP(b)-SP(a) is determined for a monomer unit derived from each monomer (b).
[0124] Monomer (b) is not limited as long as it satisfies the conditions of SP(b)-SP(a), but for example, a monomer satisfying the conditions of SP(b)-SP(a) selected from the following monomers can be used. Monomer (b) can be used alone or in combination of two or more thereof.
[0125] Monomers having a nitrile group: for example, acrylonitrile, methacrylonitrile, and the like.
[0126] Monomers having a hydroxyl group: for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.
[0127] Monomers having an amide group: for example, acrylamide, and monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method.
[0128] Monomers having a carbamate group: For example, a carbamate group is prepared by reacting an alcohol having an ethylenically unsaturated bond and having 2 to 22 carbon atoms (such as 2-hydroxyethyl methacrylate and vinyl alcohol) with an isocyanate having 1 to 30 carbon atoms [monoisocyanate compounds (such as benzenesulfonyl isocyanate, p-toluenesulfonyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, tert-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, 2-isocyanate] ethylhexyl ester, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, and 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate , and 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate, etc.), and aromatic diisocyanate compounds (phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate, etc.)] obtained by reacting the monomers by a known method;
[0129] By making an alcohol having 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, amyl alcohol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecanol, lauryl alcohol, dodecanol, myristyl alcohol, pentadecanol, hexadecanol, heptadecanol, stearyl alcohol, isostearyl alcohol, ellaidyl alcohol A monomer obtained by reacting an ethylenically unsaturated bond with an isocyanate having 2 to 30 carbon atoms [2-isocyanatoethyl (meth) acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth) acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth) acrylate, and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate] by a known method, and
[0130] Monomers having a urea group: for example, monomers obtained by reacting an amine having 3 to 22 carbon atoms [primary amines (n-butylamine, tert-butylamine, propylamine, and isopropylamine, etc.), secondary amines (di-n-ethylamine, di-n-propylamine, and di-n-butylamine, etc.), aniline, and cyclohexylamine, etc.] with an isocyanate having an ethylenically unsaturated bond and having 2 to 30 carbon atoms by a known method, and the like; and
[0131] Monomers having a carboxyl group: for example, methacrylic acid, acrylic acid, and 2-carboxyethyl (meth)acrylate.
[0132] The following embodiments of the toner of the present disclosure are also preferred.
[0133] The toner particles further contain a non-crystalline resin, and
[0134] When the SP value of amorphous resin is changed from SP(B)(J / cm 3 ) 0.5 The SP value of crystalline resin is represented by SP(A)(J / cm 3 ) 0.5 When expressed, the following is satisfied:
[0135] 3.0≥|SP(B)-SP(A)|≥0.0.
[0136] When |SP(B)-SP(A)| is 3.0 or less, the non-crystalline resin and the crystalline resin are easily compatible with each other. Therefore, the non-crystalline resin and the crystalline resin are fully mixed, and the crystalline resin can be made less likely to break. As a result, better scratch resistance of the image can be obtained.
[0137] |SP(B)-SP(A)| is preferably 0.0 to 2.6, and more preferably 0.0 to 2.3. In addition, SP(A) is preferably 19.0 (J / cm3 ) 0.5 to 26.0(J / cm 3 ) 0.5 , and more preferably 20.0 (J / cm 3 ) 0.5 To 25.0(J / cm 3 ) 0.5 .
[0138] In addition, SP(B) is preferably 20.0 (J / cm 3 ) 0.5 to 24.0(J / cm 3 ) 0.5 , and more preferably 20.5 (J / cm 3 ) 0.5 to 23.0(J / cm 3 ) 0.5 .
[0139] SP(A) and SP(B) can be controlled by the types and content ratios of monomers used in the crystalline resin and the non-crystalline resin.
[0140] As the non-crystalline resin, a resin generally used for toner can be used. Examples thereof include polyester resins, styrene acrylic resins, polyamide resins, furan resins, epoxy resins, xylene resins, and silicone resins, etc. Among them, styrene acrylic resins are preferred.
[0141] The amount of the non-crystalline resin in the toner particles is preferably from 2% by mass to 40% by mass.
[0142] The crystalline resin preferably further contains a monomer unit derived from monomer (c), and the Q value of monomer (c) is smaller than the Q value of monomer (a). Here, the Q value is a parameter proposed by Alfrey and Prince, and represents the resonance stabilization effect of a substituent in the Qe theory dealing with the reactivity of a vinyl monomer.
[0143] The Q value is a value indicating the degree of conjugation when a polymerizable monomer becomes a free radical, and is a factor related to the degree and speed of the reaction during copolymerization. When the Q value is large, the polymerizable monomer tends to become a free radical, but the free radical polymerization reaction tends to be slow. When the Q value is small, the polymerizable monomer is less likely to become a free radical, but the free radical polymerization reaction tends to be fast.
[0144] When the Q value of monomer (c) is less than the Q value of monomer (a), the free radical polymerization reaction of monomer (c) takes precedence over that of monomer (a). Therefore, the connection between monomers (c) and the connection between monomers (a) are more likely to occur than the connection between monomers (c) and monomers (a). As a result, the concentration of the monomer unit derived from monomer (a) in the crystalline resin is locally increased, and the crystallization speed of the crystalline resin is increased. Therefore, better heat resistance of the image can be obtained.
[0145] The Q values of many polymerizable monomers are disclosed in "POLYMER HANDBOOK (published by Wiley-Interscience)". For polymerizable monomers not listed in "POLYMER HANDBOOK (published by Wiley-Interscience)", the Q value can be determined by the method described on page 267 of "POLYMER HANDBOOK (published by Wiley-Interscience)".
[0146] Furthermore, when the Q value of the monomer (c) is represented by Q(c), and the Q value of the monomer (a) is represented by Q(a), it is preferred that Q(a)-Q(c) is 0.210 to 0.230, and more preferably 0.210 to 0.223.
[0147] Furthermore, Q(c) is preferably 0.025 to 0.040, and more preferably 0.027 to 0.040. Furthermore, Q(a) is preferably 0.20 to 0.30.
[0148] When a plurality of monomers satisfying the requirements of the monomer (a) are present in the crystalline resin, the value of Q(a) is a weighted average value of the Q values of the monomer units.
[0149] For example, when the monomer units derived from the monomer (a) having a Q value of Q1(a) are contained at A mol% based on the number of moles of all monomer units satisfying the requirement of the monomer units derived from the monomer (a), and when the monomer units derived from the monomer (a) having a Q value of Q2(a) are contained at (100-A) mol% based on the number of moles of all monomer units satisfying the requirement of the monomer units derived from the monomer (a), Q(a) is
[0150] Q(a)=(Q1(a)×A+Q2(a)×(100-A)) / 100.
[0151] When three or more monomer units satisfying the requirements of the monomer unit derived from monomer (a) are included, similar calculation is performed. Q(c) is also calculated in the same manner.
[0152] Furthermore, in the crystalline resin, the content ratio N(c) of the monomer units derived from the monomer (c) in all the monomer units other than the monomer units derived from the monomer (a) is 20% by mass to 100% by mass.
[0153] When N(c) is 20% by mass or more, the crystallization rate of the crystalline resin is further improved, so that more excellent heat resistance of the image can be obtained. N(c) is more preferably 30% by mass or more, and further preferably 50% by mass or more.
[0154] When a plurality of monomers satisfying the conditions of the monomer (c) are contained, N(c) is calculated based on the total amount of all monomers satisfying the conditions of the monomer (c).
[0155] Examples of monomers that can be used as monomer (c) include vinyl acetate, vinyl benzoate, vinyl pivalate, vinyl propionate, vinyl butyrate, tert-butyl vinyl benzoate, vinyl chloroacetate, vinyl decanoate, vinyl n-octanoate, vinyl hexanoate, vinyl chlorobenzoate, vinyl methacrylate, vinyl palmitate, vinyl stearate, vinyl trifluoroacetate, vinyl octylate, vinyl caprylate, vinyl laurate, vinyl myristate, and vinyl caproate, etc.
[0156] Among them, it is more preferred that the monomer (c) has a structure represented by the following formula (1).
[0157] R-COO-CH=CH2 (1)
[0158] In the formula, R represents a phenyl group or an alkyl group having 1 to 12 (preferably 1 to 4) carbon atoms.
[0159] Furthermore, it is more preferred that the monomer (c) is at least one selected from the group consisting of vinyl benzoate, vinyl pivalate, and vinyl propionate.
[0160] When the monomer (c) has these structures, the effect due to easy connection of the monomer (b) described later can be obtained. As a result, higher heat resistance of the image can be obtained.
[0161] Furthermore, the crystalline resin may include vinyl acetate or may not include vinyl acetate.
[0162] Regarding monomer (c), when the SP value of the monomer unit derived from monomer (c) is given by SP(c) (J / cm 3 ) 0.5 When expressing, it is preferred that the following is satisfied:
[0163] SP(c)-SP(a)≤4.0.
[0164] Satisfying SP(c)-SP(a)≤4.0 means that the polarities of monomer (a) and monomer (c) are close to each other. When a monomer (c) having a polarity close to that of monomer (a) is used, the site derived from monomer (a) in the crystalline resin and the site derived from monomer (c) in the non-crystalline resin are less likely to mix. As a result, the crack resistance of the crystalline resin can be improved, and better scratch resistance of the image can be obtained. SP(c)-SP(a) is more preferably 3.5 or less. SP(c)-SP(a) is preferably 0.0 or more, and more preferably 0.5 or more.
[0165] SP(c) is preferably 18.5(J / cm 3 ) 0.5 to 22.5(J / cm 3 ) 0.5 , and more preferably 19.0 (J / cm 3 ) 0.5 to 22.2(J / cm 3 ) 0.5 .
[0166] When a plurality of monomers satisfying the requirements of the monomer (c) are present in the crystalline resin, the value of SP(c) is a weighted average value of the SP values of the monomer units.
[0167] For example, when a monomer unit derived from monomer (c) having an SP value of SP1(c) is included at A mol% based on the number of moles of all monomer units satisfying the requirement of the monomer unit derived from monomer (c), and a monomer unit derived from monomer (c) having an SP value of SP2(c) is included at (100-A) mol% based on the number of moles of all monomer units satisfying the requirement of the monomer unit derived from monomer (c), SP(c) is
[0168] SP(c)=(SP1(c)×A+SP2(c)×(100-A)) / 100.
[0169] When three or more monomer units satisfying the requirements of the monomer unit derived from monomer (c) are included, similar calculation is performed.
[0170] Preferably, the crystalline resin further comprises a monomer unit derived from the monomer (b), and when the SP value of the monomer unit derived from the monomer (c) is SP(c) (J / cm 3 ) 0.5 The SP value of the monomer unit derived from monomer (b) is represented by SP(b) (J / cm 3 ) 0.5 When expressed, the following is satisfied:
[0171] SP(b)-SP(c)≥3.0.
[0172] Satisfying SP(b)-SP(c)≥3.0 means that the polarity of monomer (c) and monomer (b) is separated. By using a monomer (b) having a polarity different from that of monomer (c), monomers (c) can be more easily connected to each other. Therefore, monomers (b) can be easily connected to each other, and the crystallization speed of the crystalline resin is improved. As a result, better heat resistance of the image can be obtained.
[0173] SP(b)-SP(c) is more preferably 4.0 or more. SP(b)-SP(c) is preferably 9.0 or less, and more preferably 8.0 or less. SP(c) and SP(b) are determined by the molecular structures of monomer (c) and monomer (b).
[0174] With respect to SP(c) calculated by the above method, monomer (b) corresponds to all monomer units satisfying the following formula:
[0175] SP(b)-SP(c)≥3.0.
[0176] That is, when a plurality of monomers (b) are present, SP(b) represents the SP value of a monomer unit derived from each monomer, and SP(b)-SP(c) is determined for the monomer unit derived from each monomer (b).
[0177] Furthermore, the crystalline resin may contain a monomer unit derived from a monomer other than the above-mentioned monomers (a) to (c) as long as the above-mentioned numerical range is not impaired.
[0178] Examples of monomers other than monomers (a) to (c) include styrene and derivatives thereof such as styrene and o-methylstyrene, and (meth)acrylates such as methyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0179] The toner particles of the present disclosure may contain wax, but the amount of the wax in the toner particles is 1 part by mass to 20 parts by mass relative to 100 parts by mass of the crystalline resin.
[0180] Examples of wax are shown below.
[0181] For example, esters of monohydric alcohols and monocarboxylic acids such as behenyl behenate, stearyl stearate, and palmityl palmitate; esters of dicarboxylic acids and monohydric alcohols such as dibehenyl sebacate; esters of dihydric alcohols and monocarboxylic acids such as ethylene glycol distearate and hexylene glycol dibehenate; esters of trihydric alcohols and monocarboxylic acids such as tribehenyl glycerol; esters of tetrahydric alcohols and monocarboxylic acids such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; esters of dipentaerythritol hexastearate , and esters of hexahydric alcohols and monocarboxylic acids such as dipentaerythritol hexapalmitate; esters of polyols and monocarboxylic acids such as polyglycerol behenate; natural ester waxes such as carnauba wax and rice wax; petroleum hydrocarbon waxes and their derivatives such as paraffin, microcrystalline wax, and vaseline; hydrocarbon waxes and their derivatives obtained by the Fischer-Tropsch process; polyolefin hydrocarbon waxes and their derivatives such as polyethylene wax and polypropylene wax; higher fatty alcohols; fatty acids such as stearic acid and palmitic acid; acid amide waxes, etc.
[0182] The amount of the wax in the toner may be 5.0% by mass to 15.0% by mass, or 5.0% by mass to 10% by mass.
[0183] The toner particles may contain a colorant. Examples of the colorant include a black colorant, a yellow colorant, a magenta colorant, and a cyan colorant.
[0184] Examples of the black colorant include carbon black and the like.
[0185] Examples of yellow colorants include yellow pigments represented by monoazo compounds; disazo compounds; condensed azo compounds; isoindolinone compounds; isoindolinone compounds; benzimidazolone compounds; anthraquinone compounds; azo metal complexes; methine compounds; and allylamide compounds. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185, etc.
[0186] Examples of magenta colorants include magenta pigments represented by monoazo compounds; condensed azo compounds; diketopyrrolopyrrole compounds; anthraquinone compounds; quinacridone compounds; basic dye lake compounds; naphthol compounds; benzimidazolone compounds; thioindigo compounds; and perylene compounds. Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Bio Red 19, etc.
[0187] Examples of cyan colorants include cyan pigments represented by copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds, etc. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.
[0188] Furthermore, various dyes generally known as colorants can be used together with the pigment.
[0189] The amount of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less relative to 100 parts by mass of the binder resin.
[0190] The toner particles may contain known materials such as a charge control agent, a charge control resin, and a pigment dispersant as necessary. In addition, the toner particles may have known materials such as an organic silicon compound or a thermosetting resin on their surfaces as necessary.
[0191] Furthermore, the toner particles may be used as a toner as they are, or may be used for a toner by mixing an external additive or the like to attach the external additive to the toner particle surface as necessary.
[0192] Examples of the external additive include inorganic fine particles selected from the group consisting of silica fine particles, alumina fine particles, and titania fine particles, or composite oxides thereof, etc. Examples of the composite oxide include silica-aluminum fine particles, strontium titanate fine particles, and the like.
[0193] The amount of the external additive added is preferably 0.01 parts by mass to 8.0 parts by mass, and more preferably 0.1 parts by mass or more and 4.0 parts by mass or less, relative to 100 parts by mass of the toner particles.
[0194] The production method of the toner is not particularly limited, and publicly known methods such as a suspension polymerization method, a dissolution suspension method, an emulsification aggregation method, and a pulverization method can be used.
[0195] The measurement methods of physical properties are described below.
[0196] <Method for measuring G*(50) / G*(30) of toner>
[0197] As a measuring apparatus, a rotational flat plate type rheometer "ARES" (manufactured by TA INSTRUMENTS) was used.
[0198] As a measurement sample, a sample prepared by weighing 0.1 g of a toner and press-molding the toner into a disk shape having a diameter of 8.0 mm and a thickness of 1.5±0.3 mm by using a tablet molding machine under a room temperature (25° C.) environment is used.
[0199] The sample was mounted on a parallel plate with a diameter of 8.0 mm, heated from room temperature (25°C) to 100°C within 5 minutes and maintained for 3 minutes, and cooled to 25°C over 10 minutes. Then, the measurement was started after the temperature was maintained at 25°C for 30 minutes. At this time, the sample was set so that the initial normal force became 0. In addition, as described below, in subsequent measurements, the influence of the normal force can be offset by setting the automatic tension adjustment (Auto Tension Adjustment ON). The measurement was performed under the following conditions.
[0200] (1) Use a parallel plate with a diameter of 8.0 mm.
[0201] (2) Set the frequency to 1 Hz.
[0202] (3) The initial value of the applied strain (Strain) was set to 0.05%.
[0203] (4) The measurement was performed in the temperature range of 25°C to 60°C at a ramp rate of 2.0 [°C / min]. The measurement was performed under the following automatic adjustment mode setting conditions. The measurement was performed in the automatic strain adjustment mode (Auto Strain).
[0204] (5) Set the maximum strain (Max Applied Strain) to 20.0%.
[0205] (6) The maximum torque (Max Allowed Torque) is set to 200.0 [g·cm] and the minimum torque (MinAllowed Torque) is set to 0.2 [g·cm].
[0206] (7) Set the strain adjustment to 20.0% of the current strain. During the measurement, use the automatic tension adjustment mode.
[0207] (8) Set Auto Tension Direction to Compression.
[0208] (9) Set the Initial Static Force to 10 g and the Automatic Tension Sensitivity to 10.0 g.
[0209] (10) The operating conditions for Auto Tension are that the Sample Modulus is 1.00×10 6 Pa or more.
[0210] When measuring at a frequency of 1 Hz under the above conditions, the complex elastic modulus G* at 30 °C is represented by G*(30), and the complex elastic modulus G* at 50 °C is represented by G*(50), and G*(50) / G*(30) is calculated.
[0211] <Measurement methods for Tc, Tc', Tm, Tm' and ΔH, ΔH'>
[0212] When only one exothermic peak or endothermic peak appears, or even when multiple peaks appear, but the toner particles do not contain wax, or the amount of wax in the toner particles is less than 1 part by mass relative to 100 parts by mass of the crystalline resin, Tc, Tm and ΔH can be measured by the following method.
[0213] Use a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) to measure Tc, Tc', Tm, Tm' and ΔH, ΔH'. The melting points of indium and zinc are used for temperature calibration of the device detector, and the heat of fusion of indium is used for calibration of the calorific value.
[0214] Specifically, accurately weigh 1 mg of toner and place it in an aluminum pan. Use an empty aluminum pan as a reference. Heat from 0 °C to 150 °C at a heating rate of 10 °C / min and maintain at 150 °C for 5 minutes. Then, cool from 150 °C to 0 °C at a cooling rate of 10 °C / min. Among the exothermic peaks generated during this cooling process, take the peak temperature of the exothermic peak originating from the crystalline resin as Tc (°C).
[0215] Subsequently, after maintaining the temperature at 0 °C for 5 minutes, heat from 0 °C to 150 °C at a heating rate of 10 °C / min. At this time, among the endothermic peaks generated in the DSC curve, take the peak temperature at the endothermic peak originating from the crystalline resin as Tm (°C), and take the heat absorption as ΔH (J / g).
[0216] In the case where there are multiple exothermic peaks and endothermic peaks and it is not possible to distinguish the peaks originating from the crystalline resin and the peaks originating from wax, which is the case where the amount of wax in the toner particles is 1 part by mass to 20 parts by mass relative to 100 parts by mass of the crystalline resin, take the maximum exothermic peak and the maximum endothermic peak measured by the following method as Tc' and Tm' respectively.
[0217] Tc', Tm' and endothermic heat ΔH' were measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments). The melting points of indium and zinc were used for temperature correction of the detector of the device, and the heat of fusion of indium was used for correction of heat.
[0218] Specifically, 1 mg of the toner was accurately weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference. The temperature was raised from 0°C to 150°C at a heating rate of 10°C / min and maintained at 150°C for 5 minutes. Then, the temperature was cooled from 150°C to 0°C at a cooling rate of 10°C / min. Among the exothermic peaks generated during the temperature drop, the peak temperature of the exothermic peak with the largest exothermic heat was Tc' (°C).
[0219] Subsequently, after the temperature was maintained at 0° C. for 5 minutes, the temperature was raised from 0° C. to 150° C. at a heating rate of 10° C. / min. At this time, among the endothermic peaks generated in the DSC curve, the peak temperature at the endothermic peak having the largest endothermic amount was taken as Tm' (° C.), and the endothermic amount was taken as ΔH' (J / g).
[0220] <Method for measuring glass transition temperature of crystalline resin>
[0221] The glass transition temperature (Tg) of the crystalline resin was measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments). The melting points of indium and zinc were used for temperature correction of the detector of the device, and the heat of fusion of indium was used for correction of heat.
[0222] Specifically, 1 mg of crystalline resin was accurately weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference. Using the adjustment measurement mode, measurements were performed in the range of 0°C to 120°C under the temperature adjustment conditions of 1°C / min heating rate and ±0.6°C / 60 seconds. Since the specific heat change is obtained during the heating process, the intersection of the line at the midpoint of the baseline before and after the specific heat change occurs and the differential thermal curve is taken as the glass transition temperature (Tg).
[0223] When the endothermic peaks of crystalline resins, waxes, etc. overlap in the temperature range where the specific heat change occurs, the specific heat change occurs before and after the endothermic peak. In this case, the intersection of a straight line connecting the endothermic start temperature (starting temperature) and the endothermic end temperature (offset temperature) of the endothermic peak and a line midway between the baselines before and after the specific heat change occurs is taken as the glass transition temperature (Tg).
[0224] <Method for Identifying Monomer (a), Monomer (b), and Monomer (c) of Crystalline Resin, and Method for Measuring Content Ratio of Monomer Units Derived from Each Monomer>
[0225] The identification of various monomers in the crystalline resin and the measurement of the content ratio of the monomer units derived from each monomer are carried out by 1 H-NMR was performed under the following conditions.
[0226] Measuring apparatus: FT NMR apparatus JNM-EX400 (manufactured by JEOL Ltd.)
[0227] Measuring frequency: 400MHz
[0228] Pulse condition: 5.0μs
[0229] Frequency range: 10,500Hz
[0230] Cumulative times: 64 times
[0231] Measurement temperature: 30℃
[0232] Sample: prepared by placing 50 mg of a crystalline resin as a measurement sample in a sample tube having an inner diameter of 5 mm, adding deuterated chloroform (CDCl 3 ) as a solvent, and dissolving in a constant temperature bath at 40° C.
[0233] In the obtained 1 In the H-NMR spectrum, from the peaks attributable to the components derived from the monomer unit of the monomer (a), a peak independent of the peaks attributable to the components derived from the monomer unit of other monomers is selected, and the integrated value S1 of the peak is calculated.
[0234] Similarly, from among the peaks attributable to the components derived from the monomer unit of the monomer (b), a peak independent of the peaks attributable to the components derived from the monomer unit of other monomers is selected, and the integrated value S2 of the peak is calculated.
[0235] Furthermore, similarly, from the peaks attributable to components derived from monomer units of monomer (c) and other monomers, peaks independent of the peaks attributable to components derived from monomer units of other monomers are selected, and the integrated values of these peaks (S3 and Sx, respectively) are calculated.
[0236] By using the integrated values S1, S2, S3 and Sx, the content ratio of the monomer unit derived from the monomer (a) is determined in the following manner: Here, n1, n2, n3, and nx are each the number of hydrogen atoms in the component to which the peak observed in each part belongs.
[0237] Content ratio of monomer units derived from monomer (a) (mol%) =
[0238] {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3)+(Sx / nx))}×100
[0239] Similarly, the content ratio of the monomer units derived from the monomer (b) and the monomer (c) is determined as follows.
[0240] Content ratio of monomer units derived from monomer (b) (mol%) =
[0241] {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3)+(Sx / nx))}×100.
[0242] Content ratio of monomer units derived from monomer (c) (mol%) =
[0243] {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3)+(Sx / nx))}×100.
[0244] When a monomer not containing a hydrogen atom is used for a component other than a vinyl group in a crystalline resin, 13 C-NMR, set the measurement core to 13 C, measured in single pulse mode and with 1 The calculation was performed in the same manner as in H-NMR.
[0245] In addition, when the toner is produced by the suspension polymerization method, the peaks of the release agent and other resins overlap, and independent peaks cannot be observed. As a result, the content ratio of the monomer units derived from various monomers in the crystalline resin cannot be calculated. In that case, the crystalline resin ' can be produced by performing the same suspension polymerization without using a release agent or other resins, and the crystalline resin ' can be analyzed by treating it as a crystalline resin.
[0246] <Calculation Method of SP Values of Units Derived from Monomer (a), Monomer (b), and Monomer (c) (SP(a), SP(b), and SP(c) respectively)>
[0247] The SP value (SP(a), SP(b), SP(c)) of each monomer was obtained in the following manner according to the calculation method proposed by Fedors.
[0248] For atoms or atomic groups having a molecular structure in which double bonds of each monomer are broken by polymerization, evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol), and (4.184×ΣΔei / ΣΔvi) 0.5 Taken as SP value (J / cm 3 ) 0.5 .
[0249] <Calculation Method of SP Values SP(A) and SP(B) of Crystalline Resins and Non-Crystalline Resins>
[0250] For each monomer unit, the evaporation energy (Δei) and molar volume (Δvi) of the monomer unit constituting the resin are determined, the product thereof with the molar ratio (j) of each monomer unit in the resin is calculated, and the SP value (SP(A)) of the crystalline resin is calculated by the following formula.
[0251] Formula: SP(A)={(Σj×ΣΔei) / (Σj×ΣΔvi)} 1 / 2
[0252] The SP value (SP(B)) of the non-crystalline resin is also calculated in the same manner.
[0253] The unit of SP value in this disclosure is (J / cm 3 ) 0.5 , but can be converted to (cal / cm 3 ) 0.5 :
[0254] 1(cal / cm 3 ) 0.5 =2.046×10 -3 (J / cm 3 ) 0.5 .
[0255] <Method for measuring the acid value of resin>
[0256] The acid value is the weight (mg) of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of each resin in the present disclosure is measured according to JIS K0070-1992, but specifically, is measured according to the following procedure.
[0257] (1) Preparation of reagents
[0258] A total of 1.0 g of phenolphthalein was dissolved in 90 mL of ethanol (95 volume %), and ion-exchanged water was added to make 100 mL to obtain a phenolphthalein solution.
[0259] A total of 7g of special grade potassium hydroxide is dissolved in 5mL water, and ethanol (95 volume %) is added to make 1L. The solution is placed in an alkali-resistant container, to avoid contact with carbon dioxide etc., it is placed for 3 days, then filtered to obtain potassium hydroxide solution. The potassium hydroxide solution obtained is stored in an alkali-resistant container. A total of 25mL of 0.1mol / L hydrochloric acid is placed in a conical flask, a few drops of phenolphthalein solution are added, titrated with potassium hydroxide aqueous solution, and the factor of the potassium hydroxide solution is determined by the amount of potassium hydroxide solution required for neutralization. The 0.1mol / L hydrochloric acid used above is prepared according to JIS K 8001-1998.
[0260] (2) Operation
[0261] (A) Main test
[0262] A total of 2.0 g of each pulverized resin sample is weighed into a 200 mL conical flask, and a mixed solution of 100 mL of toluene / ethanol (2:1) is added to dissolve the sample over 5 h. Then, a few drops of phenolphthalein solution are added as an indicator, and titration is performed using potassium hydroxide solution. The end point of the titration is when the light red color of the indicator lasts for 30 seconds.
[0263] (B) Blank test
[0264] The same titration as in the above operation was performed except that no sample was used (ie, only a mixed solution of toluene / ethanol (2:1) was used).
[0265] (3) The obtained result was substituted into the following formula to calculate the acid value.
[0266] A=[(CB)×f×5.61] / S
[0267] Here, A: acid value (mgKOH / g), B: amount of potassium hydroxide solution added in the blank test (mL), C: amount of potassium hydroxide solution added in the main test (mL), f: factor of potassium hydroxide solution, and S: mass of sample (g).
[0268] <Method for measuring weight average molecular weight Mw of resin>
[0269] The weight average molecular weight (Mw) of each resin is measured by gel permeation chromatography (GPC) in the following manner.
[0270] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. Then, the obtained solution was filtered through a solvent-resistant membrane filter "Myshori Disc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution was adjusted so that the concentration of the component soluble in THF was 0.8% by mass. The sample solution was used for measurement under the following conditions.
[0271] Instrument: HLC8120 GPC (detector: RI) (manufactured by Tosoh)
[0272] Column: Seven-link column, Shodex KF-801, 802, 803, 804, 805, 806, and 807 (manufactured by Showa Denko KK)
[0273] Eluent: Tetrahydrofuran (THF)
[0274] Flow rate: 1.0mL / min
[0275] Oven temperature: 40.0℃
[0276] Sample injection volume: 0.10mL
[0277] When calculating the molecular weight of the sample, a molecular weight calibration curve prepared using a standard polystyrene resin (e.g., trade names “TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, and A-500”, manufactured by Tosoh Corporation) is used.
[0278] Example
[0279] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples. Unless otherwise specified, in the examples, parts are based on mass. The unit of each SP value in the table is (J / cm 3 ) 0.5 .
[0280] <Production Example of Non-Crystallinity Resin 1>
[0281] The following materials were added to an autoclave equipped with a decompression device, a water separator, a nitrogen introduction device, a temperature measuring device, and a stirrer.
[0282] - 32.3 parts of terephthalic acid (50.0 mol%)
[0283] - 67.7 parts (50.0 mol%) of bisphenol A-propylene oxide 2 mol adduct
[0284] -Potassium oxalate (catalyst) 0.02 parts
[0285] Subsequently, a reaction was carried out at 220° C. under normal pressure in a nitrogen atmosphere until a desired molecular weight was reached. After the temperature was lowered, the mixture was pulverized to obtain a non-crystalline resin 1.
[0286] The obtained non-crystalline resin 1 had a weight average molecular weight (Mw) of 20,000, a glass transition temperature (Tg) of 70° C., and an acid value of 5.1 mgKOH / g. In addition, the SP value (SP(B)) of the non-crystalline resin 1 was 22.3 (J / cm 3 ) 0.5 .
[0287] <Production Example of Non-Crystallinity Resin 2>
[0288] Under a nitrogen atmosphere, the following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube.
[0289]
[0290] The components in the reaction vessel are stirred at 200 rpm and heated to 70°C to carry out a polymerization reaction for 12 hours to obtain a solution in which the polymer of the monomer composition is dissolved in toluene. Subsequently, after the solution is cooled to 25°C, the solution is poured into 1000.0 parts of methanol under stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter is filtered out, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain non-crystalline resin 2. The weight average molecular weight (Mw) of the obtained non-crystalline resin 2 is 22,000, the glass transition temperature (Tg) is 75°C, and the acid value is 21.1 mgKOH / g. The SP value (SP(B)) of non-crystalline resin 2 is 21.6 (J / cm 3 ) 0.5 .
[0291] <Production Example of Non-Crystallinity Resin 3>
[0292] Under a nitrogen atmosphere, the following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube.
[0293]
[0294] The components in the reaction vessel are stirred at 200 rpm and heated to 70°C to carry out a polymerization reaction for 12 hours to obtain a solution in which the polymer of the monomer composition is dissolved in toluene. Subsequently, after the solution is cooled to 25°C, the solution is poured into 1000.0 parts of methanol under stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter is filtered out, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain non-crystalline resin 3. The weight average molecular weight (Mw) of the obtained non-crystalline resin 3 is 20,000, the glass transition temperature (Tg) is 93°C, and the acid value is 21.3 mgKOH / g. The SP value (SP(B)) of the non-crystalline resin 3 is 20.3 (J / cm3 ) 0.5 .
[0295] <Production Example of Non-Crystallinity Resin 4>
[0296] The following materials were added to an autoclave equipped with a decompression device, a water separator, a nitrogen introduction device, a temperature measuring device, and a stirrer.
[0297]
[0298]
[0299] Subsequently, a reaction was carried out at 220° C. under normal pressure in a nitrogen atmosphere until a desired molecular weight was reached. After the temperature was lowered, the mixture was pulverized to obtain a non-crystalline resin 4.
[0300] The obtained non-crystalline resin 4 had a weight average molecular weight (Mw) of 80,000, a glass transition temperature (Tg) of 74° C., and an acid value of 10.1 mgKOH / g. In addition, the SP value (SP(B)) of the non-crystalline resin 4 was 22.3 (J / cm 3 ) 0.5 .
[0301] <Production Example of Crystalline Resin 1>
[0302] Under a nitrogen atmosphere, the following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube.
[0303] -Solvent: 100.0 parts of toluene
[0304] -Monomer composition 100.0 parts
[0305] (A monomer composition is obtained by mixing the following behenyl acrylate (monomer unit SP value: 18.3, monomer SP value: 17.7), methacrylonitrile (monomer unit SP value: 26.0, monomer SP value: 22.0), and n-butyl acrylate (monomer unit SP value: 20.0, monomer SP value: 18.0) in the ratio shown below)
[0306]
[0307] The components in the reaction vessel were stirred at 200 rpm and heated to 70°C to carry out a polymerization reaction for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Subsequently, after the solution was cooled to 25°C, the solution was poured into 1000.0 parts of methanol under stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered out, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain crystalline resin 1. The weight average molecular weight (Mw) of the obtained crystalline resin 1 was 54,000, the acid value was 0.0 mgKOH / g, and the melting point was 58°C. The SP value (SP(A)) of crystalline resin 1 was 23.8 (J / cm 3 ) 0.5 .
[0308] When the crystalline resin 1 was analyzed by NMR, 22.4 mol% of a monomer unit derived from behenyl acrylate was contained, 69.8 mol% of a monomer unit derived from methacrylonitrile was contained, and 7.8 mol% of a monomer unit derived from n-butyl acrylate was contained.
[0309] <Production Example of Crystalline Resin 2>
[0310] The following materials were added to an autoclave equipped with a decompression device, a water separator, a nitrogen introduction device, a temperature measuring device, and a stirrer.
[0311]
[0312] Subsequently, the reaction was carried out at 220° C. under normal pressure in a nitrogen atmosphere until the weight average molecular weight Mw reached 22,000. The melting point of the obtained crystalline resin 2 was 63° C. and the acid value was 6.1 mgKOH / g. The SP value (SP(A)) of the crystalline resin 2 was 20.5 (J / cm 3 ) 0.5 .
[0313] A production example of toner is shown below.
[0314] <Production Example of Toner 1>
[0315] A mixture consisting of the following components was prepared.
[0316] -Monomer (b): 50.0 parts (80.3 mol%) of methacrylonitrile
[0317] -Other monomers: n-butyl acrylate 10.0 parts (8.4 mol%)
[0318] -Colorant: Pigment Blue 15:3 6.5 parts
[0319] The above mixture was put into an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.) and dispersed at 200 rpm for 2 hours using zirconia beads having a diameter of 5 mm to obtain a raw material dispersion.
[0320] At the same time, 735.0 parts of ion exchange water and 16.0 parts of trisodium phosphate (dodecahydrate) were added to a container equipped with a high-speed stirring device Homomixer (manufactured by Primix Corporation) and a thermometer, and the mixture was stirred at 12000 rpm while being heated to 60°C. An aqueous solution of calcium chloride in which 9.0 parts of calcium chloride (dihydrate) were dissolved in 65.0 parts of ion exchange water was added to the mixture, and the mixture was stirred at 12,000 rpm for 30 minutes while being maintained at 60°C. The pH was adjusted to 6.0 by adding 10% hydrochloric acid to obtain an aqueous medium in which an inorganic dispersion stabilizer including hydroxyapatite was dispersed in water.
[0321] Subsequently, the raw material dispersion was transferred to a container equipped with a stirrer and a thermometer, and the temperature was raised to 60° C. while stirring at 100 rpm.
[0322] -Monomer (a): 40.0 parts (11.3 mol%) of behenyl acrylate
[0323] - 15.0 parts of non-crystalline resin
[0324] The above materials were added and stirred at 100 rpm for 30 minutes while maintaining 60° C., and then 5.0 parts of tert-butyl peroxypivalate (Perbutyl PV, manufactured by NOF Corporation) was added as a polymerization initiator, followed by stirring for 1 minute. The mixture was then put into an aqueous medium stirred at 12,000 rpm with a high-speed stirring device. Stirring was continued at 12,000 rpm for 20 minutes with the above high-speed stirring device while maintaining 60° C. to obtain a granulation liquid.
[0325] The granulation liquid was transferred to a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube, and heated to 70° C. while stirring at 150 rpm in a nitrogen atmosphere. A polymerization reaction was performed at 150 rpm for 12 hours while maintaining 70° C. to obtain a toner particle dispersion.
[0326] The obtained toner particle dispersion was cooled to 20° C. while stirring at 150 rpm, and then diluted hydrochloric acid was added while stirring until the pH became 1.5 to dissolve the dispersion stabilizer. The solid content was filtered out, washed sufficiently with ion exchange water, and then vacuum dried at 40° C. for 24 hours to obtain toner particles 1.
[0327] With respect to 100.0 parts of the obtained toner particles 1, a total of 2.0 parts of silica fine particles (hydrophobicized with hexamethyldisilazane, primary particle number average particle diameter: 10 nm, BET specific surface area: 170 m 2 / g), and mixing was performed using a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) at 3000 rpm for 15 minutes to obtain Toner 1.
[0328] In addition, in the production example of toner 1, the same production was carried out without including a colorant and a non-crystalline resin to obtain crystalline resin '1. The weight average molecular weight of crystalline resin '1 was 42,000, the acid value was 0.0 mgKOH / g, and the melting point was 60°C. When crystalline resin '1 was analyzed by NMR, 11.3 mol% of monomer units derived from behenyl acrylate, 80.3 mol% of monomer units derived from methacrylonitrile, and 8.4 mol% of monomer units derived from n-butyl acrylate were contained. The physical property values of crystalline resin '1 were taken as the physical property values of the crystalline resin used for toner particles 1.
[0329] <Production Example of Toner Particles 2 to 10 and 24 to 28, Crystalline Resins 2 to 10 and 24 to 28, and Toners 2 to 10 and 24 to 28>
[0330] Toner particles 2 to 10 and 24 to 28, crystalline resins '2 to 10 and 24 to 28, and toners 2 to 10 and 24 to 28 were obtained in the same manner as in the production example of toner 1, except that the kind and addition amount of the monomer and the kind and amount of the non-crystalline resin were changed as shown in Table 1. The physical property values of the crystalline resins '2 to 10 and 24 to 28 were taken as the physical property values of the crystalline resin used for toner particles 2 to 10 and 24 to 28.
[0331] <Production Example of Toner Particles 16, Crystalline Resin '16 and Toner 16>
[0332] Toner particles 16, crystalline resin '16, and toner 16 were obtained in the same manner as in the production example of toner 1, except that 50.0 parts of methacrylonitrile (monomer (b)) and 10.0 parts of n-butyl acrylate (other monomers) in the mixture in the production example of toner 1 were changed to 36.0 parts of vinyl acetate (monomer (c)) and 24.0 parts of methacrylonitrile (monomer (b)). The physical property values of the obtained crystalline resin '16 were taken as the physical property values of the crystalline resin used for toner particles 16.
[0333] <Production Example of Toner Particles 17 to 23 and 29 to 31, Crystalline Resins 17 to 23 and 29 to 31, and Toners 17 to 23 and 29 to 31>
[0334] Toner particles 17 to 23 and 29 to 31, crystalline resins '17 to 23 and 29 to 31, and toners 17 to 23 and 29 to 31 were obtained in the same manner as in the production example of toner 16, except that 36.0 parts of vinyl acetate in the mixture in the production example of toner 16 was changed to monomer (c) shown in Table 2, and 24.0 parts of methacrylonitrile in the mixture was changed to monomer (b) shown in Table 2. The physical property values of the crystalline resins '17 to 23 and 29 to 31 were taken as the physical property values of the crystalline resin used for toner particles 17 to 23 and 29 to 31.
[0335]
[0336]
[0337] <Production Example of Toner 11>
[0338] - Crystalline resin 1 95.0 parts
[0339] - Non-crystalline resin 4 5.0 parts
[0340] -CI Pigment Blue 15:3 6.5 parts
[0341] - Charge control agent (T-77: manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts
[0342] The above materials were pre-mixed with an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.), and then melt-kneaded with a twin-screw kneading extruder (PCM-30 model, manufactured by Ikegai Iron Works Co., Ltd.).
[0343] The obtained kneaded product was cooled, coarsely pulverized with a hammer mill and then pulverized with a mechanical pulverizer (T-250 manufactured by Turbo Industries, Ltd.), and the obtained finely pulverized powder was classified with a multi-component classifier using Coanda effect to obtain toner particles 11 .
[0344] External addition of Toner Particles 11 was performed in the same manner as in Example 1 to obtain Toner 11 .
[0345] <Production Example of Toners 12 to 15 and 32>
[0346] Toner particles 12 to 15 and 32 and toners 12 to 15 and 32 were obtained in the same manner as in the production example of toner 11, except that the kind and addition amount of the resin and the kind and addition amount of the wax were changed as shown in Table 3.
[0347] [Table 3]
[0348]
[0349] The physical properties of the obtained Toners 1 to 32 were measured using the above-described methods. Tables 4 and 5 show the measurement results of the physical properties of the crystalline resin contained in each toner particle.
[0350]
[0351]
[0352] Tables 6 and 7 show the measurement results of the physical properties of each toner particle.
[0353] [Table 6]
[0354]
[0355] [Table 7]
[0356]
[0357] The properties of the obtained toners 1 to 32 were evaluated according to the following methods.
[0358] <Low Temperature Fixability>
[0359] The toner was taken out from a commercially available cyan cartridge, and 50 g of the toner to be evaluated was filled in the cartridge. The process cartridge filled with the toner to be evaluated was left in a normal temperature and humidity environment (temperature 23° C., relative humidity 50%) for 48 hours.
[0360] The process cartridge was mounted on a Canon laser beam printer LBP-7700C modified so as to be operable even if the fixing device was removed, and using the printer, an unfixed image of an image pattern in which square images of 10 mm × 10 mm were evenly arranged at 9 points across the transfer paper was output. The toner load on the transfer paper was 0.80 mg / cm 2 , and use Fox River Bond (90g / m 2 ) as transfer paper.
[0361] The output unfixed image was fixed using an external fixing device. A device obtained by taking out the fixing device from LBP-7700C and making it run even without a laser beam printer was used as the external fixing device. The process speed of the external fixing device was set to 330 mm / sec, the initial fixing temperature was set to 100°C, the set temperature was gradually increased by 5°C, and the unfixed image was fixed at each temperature.
[0362] The images fixed at each fixing temperature were placed under 4.9 kPa (50 g / cm 2 ) were rubbed back and forth 5 times with Sylbon paper (manufactured by Ozu Corporation: DUSPER K-3) under a load of 1.5 %. The image density before and after rubbing was measured with a Macbeth reflection densitometer (manufactured by Macbeth), the temperature at which the image density reduction rate before and after rubbing became 20% or less was set as the fixing start temperature, and the low temperature fixing property was evaluated according to the following criteria.
[0363] A: The fixing start temperature is lower than 110℃
[0364] B: The fixing start temperature is 110°C or higher and lower than 120°C
[0365] C: Fixing start temperature is 120°C or higher and lower than 130°C
[0366] D: The fixing start temperature is 130°C or higher and lower than 140°C
[0367] E: Fixing start temperature is 140°C or higher and lower than 150°C
[0368] F: Fixing start temperature is above 150°C
[0369] <Heat resistance of images>
[0370] The unfixed image of 6.0 cm in length and 5.0 cm in width was output on the transfer paper. The toner load on the transfer paper was 0.80 mg / cm 2 , and use Fox River Bond (90g / m 2 The following evaluations were performed on image papers on which an unfixed image was fixed at a temperature 20° C. higher than the fixing start temperature of each toner.
[0371] Place the fixed image paper with the image part facing down on 100 sheets of unused paper (Fox River Bond (90g / m 2)) and further 2500 sheets of unused paper of the same kind are placed on the fixed image paper, thereby sandwiching the fixed image paper. The stack is left to stand in a thermostatic bath adjusted to 55°C for 24 hours and then taken out from the thermostatic bath. The reflectivity of the portion of the unused paper in contact with the fixed image paper that contacts the image portion is measured. The color transfer of the image is measured by subtracting the reflectivity of the portion of the unused paper that does not contact the image portion from the obtained reflectivity. The heat resistance of the image is evaluated from the reflectivity after subtraction according to the following standard. The reflectivity is measured with TC-6DS (manufactured by Tokyo Denshoku Co., Ltd.).
[0372] A: The reflectivity after subtraction is less than 2.0%
[0373] B: The reflectivity after subtraction is 2.0% or more and less than 3.0%
[0374] C: The reflectivity after subtraction is 3.0% or more and less than 5.0%
[0375] D: The reflectivity after subtraction is 5.0% or more and less than 8.0%
[0376] E: The reflectivity after subtraction is 8.0% or more and less than 10.0%
[0377] F: Reflectivity after subtraction is 10.0% or more
[0378] <Image Scratch Resistance>
[0379] The unfixed image of 6.0 cm in length and 5.0 cm in width was output on the transfer paper. The amount of toner on the transfer paper was 0.80 mg / cm 2 , and use Fox River Bond (90g / m 2 The following evaluations were performed on image papers on which an unfixed image was fixed at a temperature 20° C. higher than the fixing start temperature of each toner.
[0380] Based on 4.9kPa (50g / cm 2 The abrasion resistance of the fixed image was evaluated by the image density reduction rate before and after rubbing the fixed image with Sylbon paper (manufactured by Ozu Corporation: DUSPERK-3) at a speed of 1 reciprocating stroke per second under a load of 200 μm. The image density reduction rate was measured with a Macbeth reflection densitometer (manufactured by Macbeth).
[0381] The evaluation criteria for the scratch resistance of the fixed image are as follows.
[0382] A: Concentration reduction rate is less than 3.0%
[0383] B: Concentration reduction rate is 3.0% or more and less than 5.0%
[0384] C: Concentration reduction rate is 5.0% or more and less than 8.0%
[0385] D: Concentration reduction rate is 8.0% or more and less than 10.0%
[0386] E: Concentration reduction rate is 10.0% or more and less than 15.0%
[0387] F: Concentration reduction rate is 15.0% or more
[0388] [Table 8]
[0389]
[0390] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles containing a crystalline resin, characterized in that: The crystalline resin comprises a monomer unit derived from a monomer (a), a monomer unit derived from a monomer (b), and a monomer unit derived from a monomer (c), The monomer (a) is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, The monomer (c) has a structure represented by the following formula (1): R-COO-CH=CH2 (1) Wherein, R represents a phenyl group or an alkyl group having 1 to 12 carbon atoms, The SP value of the monomer unit derived from the monomer (c) is given by SP(c) (J / cm 3 ) 0.5 The SP value of the monomer unit derived from the monomer (b) is represented by SP(b) (J / cm 3 ) 0.5 and the SP value of the monomer unit derived from the monomer (a) is represented by SP(a) (J / cm 3 ) 0.5 Indicates that the following are satisfied: SP(b)-SP(a)≥4.0, SP(b)-SP(c)≥3.0, and SP(c)-SP(a)≤4.0, When, in the dynamic viscoelasticity measurement of the toner, the complex elastic modulus at 30° C. is represented by G*(30) and the complex elastic modulus at 50° C. is represented by G*(50), the following is satisfied: 1.00≥G*(50) / G*(30)≥0.30, And when In differential scanning calorimetry of the toner, The peak temperature of the exothermic peak derived from the crystalline resin in the process of cooling after the temperature is raised to 150° C. is represented by Tc. In the temperature increase process after the temperature decrease process, the peak temperature of the endothermic peak derived from the crystalline resin is represented by Tm, and When the amount of heat absorbed is represented by ΔH, Tm is 50.0 to 80.0°C, ΔH is 35 to 60 J / g, and Tm-Tc is 0.0 to 7.0°C.
2. A toner comprising toner particles containing a crystalline resin and a wax, characterized in that: The crystalline resin comprises a monomer unit derived from a monomer (a), a monomer unit derived from a monomer (b), and a monomer unit derived from a monomer (c), The monomer (a) is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, The monomer (c) has a structure represented by the following formula (1): R-COO-CH=CH2 (1) Wherein, R represents a phenyl group or an alkyl group having 1 to 12 carbon atoms, The SP value of the monomer unit derived from the monomer (c) is given by SP(c) (J / cm 3 ) 0.5 The SP value of the monomer unit derived from the monomer (b) is represented by SP(b) (J / cm 3 ) 0.5 and the SP value of the monomer unit derived from the monomer (a) is represented by SP(a) (J / cm 3 ) 0.5 Indicates that the following are satisfied: SP(b)-SP(a)≥4.0, SP(b)-SP(c)≥3.0, and SP(c)-SP(a)≤4.0, When, in the dynamic viscoelasticity measurement of the toner, the complex elastic modulus at 30° C. is represented by G*(30) and the complex elastic modulus at 50° C. is represented by G*(50), the following is satisfied: 1.00≥G*(50) / G*(30)≥0.30, The amount of the wax in the toner particles is 1 to 20 parts by mass relative to 100 parts by mass of the crystalline resin; and when In differential scanning calorimetry of the toner, During the cooling process after heating to 150°C, the peak temperature of the maximum exothermic peak is represented by Tc'. In the temperature-raising process after the temperature-lowering process, the peak temperature of the maximum endothermic peak is represented by Tm', and When the amount of heat absorbed is represented by ΔH', Tm' is 50.0 to 80.0°C, ΔH' is 35 to 60 J / g, and Tm'-Tc' is 0.0 to 7.0°C.
3. The toner according to claim 1 or 2, wherein The content ratio N(a) of the monomer unit derived from the monomer (a) in the crystalline resin is 30 to 60% by mass. 4 . The toner according to claim 1 , wherein an amount of the crystalline resin in the toner particles is 60 to 100% by mass. 5 . The toner according to claim 1 , wherein the crystalline resin has a glass transition temperature of 50 to 90° C.
6. The toner according to claim 1 or 2, wherein The toner particles further include a non-crystalline resin, and When the SP value of the non-crystalline resin is SP(B)(J / cm 3 ) 0.5 The SP value of the crystalline resin is represented by SP(A)(J / cm 3 ) 0.5 When expressed, the following is satisfied: 3.0≥|SP(B)-SP(A)|≥0.
0.
7. The toner according to claim 1 or 2, wherein In the crystalline resin, the content ratio N(b) of the monomer unit derived from the monomer (b) in all monomer units other than the monomer unit derived from the monomer (a) is 50% by mass to 100% by mass.
8. The toner according to claim 1 or 2, wherein The Q value of the monomer (c) is smaller than the Q value of the monomer (a), the Q value is a value indicating the degree of conjugation when a polymerizable monomer becomes a radical, and is a factor related to the degree and speed of reaction during copolymerization. 9 . The toner according to claim 8 , wherein when the Q value of the monomer (c) is represented by Q(c) and the Q value of the monomer (a) is represented by Q(a), Q(a)-Q(c) is 0.210 to 0.
230.
10. The toner according to claim 1 or 2, wherein in the crystalline resin, a content ratio N(c) of the monomer unit derived from the monomer (c) in all monomer units other than the monomer unit derived from the monomer (a) is 20 to 100% by mass. 11 . The toner according to claim 1 , wherein the monomer (c) is at least one selected from the group consisting of vinyl benzoate, vinyl pivalate, and vinyl propionate.